2019
DOI: 10.1002/acm2.12705
|View full text |Cite
|
Sign up to set email alerts
|

Use of a plastic scintillator detector for patient‐specific quality assurance of VMAT SRS

Abstract: Purpose To evaluate a scintillator detector for patient‐specific quality assurance of VMAT radiosurgery plans. Methods The detector was comprised of a 1 mm diameter, 1 mm high scintillator coupled to an acrylic optical fiber. Sixty VMAT SRS plans for treatment of single targets having sizes ranging from 3 mm to 30.2 mm equivalent diameter (median 16.3 mm) were selected. The plans were delivered to a 20 cm × 20 cm x 15 cm water equivalent plastic phantom having either the scintillator detector or radiochromic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…RCF agreed well with a plastic scintillator detector, 22 so the systematic 1.2% difference between the SRSMC and RCF suggests a difference in response of the diode array due to the non‐coplanar VMAT delivery of patient plans and the coplanar calibration geometry. Further investigation is needed to determine if this difference is consistent across multiple diode arrays and if an improved calibration technique can be developed to reduce the difference.…”
Section: Discussionmentioning
confidence: 65%
“…RCF agreed well with a plastic scintillator detector, 22 so the systematic 1.2% difference between the SRSMC and RCF suggests a difference in response of the diode array due to the non‐coplanar VMAT delivery of patient plans and the coplanar calibration geometry. Further investigation is needed to determine if this difference is consistent across multiple diode arrays and if an improved calibration technique can be developed to reduce the difference.…”
Section: Discussionmentioning
confidence: 65%
“…Our results are comparable with these studies for similar measurement positions. To improve the dose measurement, a study by Snyder and Sullivan 34 suggested calibrating the plastic scintillator dosimeter with a 4 × 4 cm 2 field size for the VMAT dose measurement. This is because the techniques are delivered in smaller segments and calibrating at smaller field size match closer to the irradiation condition.…”
Section: Discussionmentioning
confidence: 99%
“…A plastic scintillator detector needs to be calibrated before absolute dose measurement due to the Cerenkov effect, which is field-size dependent. According to the research of Snyder et al , 14 the authors found a low sensitivity to the Cerenkov factor under different sizes of calibration fields, but the residual deviations suggested that the calibration should be done under a condition similar to which the measurements will be made in. Therefore, a 10 × 10 cm 2 field was used for IMRT plan verification, and a 4 × 4 cm 2 field was used for VMAT SRS plan verification in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For determining the known dose, a Farmer-Type chamber Exradin A19 was used. According to the literature, 14 W1 was calibrated using a 6MV FFF beam and a 4 × 4 cm 2 field for VMAT SRS plans whereas a 6MV beam and a 10 × 10 cm 2 field were used for IMRT plans. Since PSD has a slight temperature dependency, all experiments were carried out at a constant temperature of 22°C with the variation being less than 1°C, so that the temperature dependency was irrelevant.…”
Section: Methodsmentioning
confidence: 99%